Penentuan Koperasi Terbaik pada Dinas Koperasi dan UMKM Kota Binjai menggunakan Metode WASPAS - Mira Asmara Zega; Imran Lubis; Kristina Anastasia Br. Sitepu (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
A cooperative is a business entity based on the principle of kinship. Cooperatives have the aim of improving the welfare of their members through the activities they carry out. The Binjai City Cooperatives and UMKM Service is a regional apparatus within the Binjai City Government for government affairs in the field of Cooperatives, Small and Medium Enterprises. The Binjai City Cooperatives and UMKM Department always carries out assessments of every cooperative in the city of Binjai in the form of an assessment of the best cooperatives which aims to increase the motivation of cooperative institutions and as an evaluation material for the performance of cooperatives recorded in the City of Binjai. In carrying out the assessment of the best cooperatives carried out by the Binjai City Cooperatives and UMKM Service, it took quite a long time. This is because the data collection and processing process is conventional and simple. To overcome existing problems, a decision support system was created to facilitate the management and calculations of each cooperative. In this research, the method used in the calculation process is WASPAS (Weighted Aggregated Sum Product Assessment). The Weighted Aggregated Sum Product Assessment (WASPAS) method is a method that is able to minimize errors or maximize the assessment to determine the highest and lowest values. The final result of this research is a decision support system that is able to produce decision recommendations in determining the best cooperative at the Binjai City Cooperative and UMKM Department.